2013
DOI: 10.7205/milmed-d-12-00440
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Perceptions of Supplement Use by U.S. Marines Deployed to Afghanistan

Abstract: Dietary supplements are implicated in an increasing number of minor and serious adverse events, including death. A series of adverse events in deployed Marines using multiple supplements prompted medical officers to investigate the prevalence of supplement use among Marines stationed on Camp Leatherneck, Afghanistan. The investigators developed a survey to identify the types of supplements used, patterns of supplement use, reasons for taking supplements, perceived benefits from using supplements, and self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…Interestingly, our findings of DS use among deployed personnel are remarkably similar to DS use by United States Marines deployed to the same region of conflict (Cassler et al 2013). Previous reports of DS use for deployed soldiers (Boos et al 2010(Boos et al , 2011Cassler et al 2013;Jacobson et al 2012) did not directly compare deployed and garrison personnel using the same survey instrument as was done in the current investigation. Therefore, this report is the first we are aware of that definitively demonstrates that patterns of DS use change during deployment.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Interestingly, our findings of DS use among deployed personnel are remarkably similar to DS use by United States Marines deployed to the same region of conflict (Cassler et al 2013). Previous reports of DS use for deployed soldiers (Boos et al 2010(Boos et al , 2011Cassler et al 2013;Jacobson et al 2012) did not directly compare deployed and garrison personnel using the same survey instrument as was done in the current investigation. Therefore, this report is the first we are aware of that definitively demonstrates that patterns of DS use change during deployment.…”
Section: Discussionsupporting
confidence: 47%
“…Also, a large cohort study reported greater use of body-building and weight-loss supplements in both males and females with a history of deployment to a combat theater (Jacobson et al 2012). Another study found greater DS use by United States Marines who were deployed to Afghanistan (Cassler et al 2013). The prevalence of overall DS use we observed among deployed personnel was much higher than the 35%-40% levels reported in the recent studies of British soldiers deployed in Afghanistan or Iraq, but this may reflect differences in the questionnaires used in each study (Boos et al 2010(Boos et al , 2011 or general differences between British and American DS use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three unique investigations in 38 publications met the review criteria. Seven reports were in government technical reports [14-20], two were only in abstract form [21,22], 9 were in an Institute of Medicine report on the use of DSs in military personnel [23-31], and 20 reports were in peer-reviewed journal articles [5-9,12,32-45]. Three individual studies had two reports each [15,19,25,30,32,38] and one produced three relevant publications [8,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Like athletes, military personnel often have occupational tasks that require intense and prolonged periods of physical activity. Like athletes, service members may use DSs that have purported ergogenic effects to enhance their occupational performance [5-9]. Unlike athletes, service members may be working in austere and hostile surroundings under extreme environmental conditions with high risk of injury.…”
Section: Introductionmentioning
confidence: 99%